Cost of electricity in Brazil: Effects of 2004 regulatory reform - Marina Figueira de Mello; Monica Barros (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
In 2004, in the beginning of the first president Lula mandate, a complete regulatory reform of electricity was launched. In 2008, four years after, Brazilian Congress started an investigation of the causes of Brazilian relatively high electricity tariffs. The results of the investigation pointed out numerous reasons, but failed to identify generation costs as one of the main causes. In this paper the analysis done by Congress is broadened addressing the trend in electricity production costs. The main conclusions are that the implementation of auctions together with subsidies from state enterprises did not reduce future acquisition costs as much as expected, but successfully reduced the rhythm of price increases. The long run marginal expansion cost is increasing very fast because new hydro plants are ever more distant of consumption centers and environmental costs are difficult to mitigate. Thermal plants and other technologies, though increasing in importance, still have much higher prices. In case prices reflected marginal incremental costs, electricity prices would have been much higher. The fact that consumers do not see such high incremental costs, allow them to take wrong consumption decisions. As consumers are able to buy at prices lower than marginal cost, consumption levels go too far. Demand increases amplify the electricity market gap and reinforce the necessity of new investments.
Keywords: L43; 330; Electricity; regulatory reform; energy auctions and generation costs. JEL Codes: L43; Elektrizitätspolitik; Wirkungsanalyse; Brasilien